Cortical thickness development of human primary visual cortex related to the age of blindness onset. - Li, Qiaojun; Song, Ming; Xu, Jiayuan; Qin, Wen; Yu, Chunshui; Jiang, Tianzi (Brain Imaging & Behavior, 2017)
Blindness primarily induces structural alteration in the primary visual cortex (V1). Some studies have found that the early blind subjects had a thicker V1 compared to sighted controls, whereas late blind subjects showed no significant differences in the V1. This implies that the age of blindness onset may exert significant effects on the development of cortical thickness of the V1. However, no previous research used a trajectory of the age of blindness onset-related changes to investigate these effects. Here we explored this issue by mapping the cortical thickness trajectory of the V1 against the age of blindness onset using data from 99 blind individuals whose age of blindness onset ranged from birth to 34 years. We found that the cortical thickness of the V1 could be fitted well with a quadratic curve in both the left (F = 11.59, P = 3 × 10-5) and right hemispheres (F = 6.54, P = 2 × 10-3). Specifically, the cortical thickness of the V1 thinned rapidly during childhood and adolescence and did not change significantly thereafter. This trend was not observed in the primary auditory cortex (A1), primary motor cortex (M1), or primary somatosensory cortex (S1). These results provide evidence that an onset of blindness before adulthood significantly affects the cortical thickness of the V1 and suggest a critical period for cortical development of the human V1.